2021
DOI: 10.1103/physrevb.104.165131
|View full text |Cite
|
Sign up to set email alerts
|

Dual current anomalies and quantum transport within extended reservoir simulations

Abstract: Quantum transport simulations are rapidly evolving and now encompass well-controlled tensor network techniques for many-body transport. One powerful approach combines matrix product states with extended reservoirs. In this method, continuous reservoirs are represented by explicit, discretized counterparts where a chemical potential or temperature drop is maintained by relaxation. Currents are strongly influenced by relaxation when it is very weak or strong, resulting in a simulation-analog of Kramers' turnover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Nonetheless, since one is forced to work with finite lead models, lead level broadening is introduced via Γ ${{\rm{\Gamma }}}$ to obtain an effectively continuous spectrum. The sensitivity of the transport calculation results to the tradeoff between lead dimensions and level broadening has been extensively studied [111,112,123–130] . Specifically, a typical Kramer's turnover behavior has been demonstrated for many model systems with a broad parameter stability regime [123,124,126–131] .…”
Section: Extensions and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, since one is forced to work with finite lead models, lead level broadening is introduced via Γ ${{\rm{\Gamma }}}$ to obtain an effectively continuous spectrum. The sensitivity of the transport calculation results to the tradeoff between lead dimensions and level broadening has been extensively studied [111,112,123–130] . Specifically, a typical Kramer's turnover behavior has been demonstrated for many model systems with a broad parameter stability regime [123,124,126–131] .…”
Section: Extensions and Applicationsmentioning
confidence: 99%
“…The sensitivity of the transport calculation results to the tradeoff between lead dimensions and level broadening has been extensively studied [111,112,123–130] . Specifically, a typical Kramer's turnover behavior has been demonstrated for many model systems with a broad parameter stability regime [123,124,126–131] . Figure 4 provides an example of the dependence of the steady‐state current on the value of the driving rate for several tight‐binding lead model sizes.…”
Section: Extensions and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5, we show the comparison of the entropy of the dot computed using our approach against the results obtained by numerically integrating the classical master equation [Eq. (50)] for increasing values of T . The plots clearly show the convergence of the results with increasing temperature, providing another benchmark for the consistency of our approach.…”
Section: Thermodynamics Of a Driven Resonant-levelmentioning
confidence: 99%
“…In this approach, the macroscopic baths are systematically approximated by a finite number of damped modes, which we call leads. Initially introduced for bosonic baths [20][21][22], this approach has been subsequently extensively used to study quantum transport in fermionic setups also [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44][45][46][47][48][49][50][51]. When combined with tensor network techniques, it has been recently shown that it is possible to completely non-perturbatively obtain energy and particle currents in non-equilibrium steady states (NESS) of interacting quantum many-body systems, and thereby the thermodynamics at NESS, using this approach [47].…”
Section: Introductionmentioning
confidence: 99%